2017
DOI: 10.1515/jgd-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Follow the Money: Remittance Responses to FDI Inflows

Abstract: Migrant networks are an important catalyst for promoting FDI flows between countries. Migrants also send increasingly large remittances to their home countries. This paper considers how these two capital flows are related, specifically examining how remittance flows respond to the amount of FDI inflows to a country. Using a panel of 118 countries over 1980–2010, we estimate a random effects model and find a positive and significant effect of FDI flows on remittances, while controlling for other standard determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…The results indicate unidirectional causality. In the other hand, Coon and Neumann (2015) studied the relationship between remittances and FDI in 118 developing countries from 1980 to 2010 and found that an increase of 10% in FDI inflows corresponds to a 3.6% increase in remittances. Such results suggest that migrant remittances and FDI are complementary.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The results indicate unidirectional causality. In the other hand, Coon and Neumann (2015) studied the relationship between remittances and FDI in 118 developing countries from 1980 to 2010 and found that an increase of 10% in FDI inflows corresponds to a 3.6% increase in remittances. Such results suggest that migrant remittances and FDI are complementary.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The existence of social ties between the migrant and the household dispels the notion of pure investment motive in remittances (Mahapatro, 2017;Coon & Neumann, 2015;Azizi, 2017). A striking feature of diaspora investment is the commonality of stimulants with other external capital flows; foreign direct and official development assistance.…”
Section: Foreign Remittances and Private Sector Investmentmentioning
confidence: 99%
“…Again some studies also showed that FDI inflows have impact on remittance receiving. Coon and Neumann (2017) analyzed how FDI inflows and remittance inflows are related. They found that FDI complements remittance and the relationship between remittances and FDI is the strongest for low income countries.…”
Section: Fdi Net Inflowsmentioning
confidence: 99%